A method for preparing poplar-based porous carbon material

Through technical means such as DC arc method and salt template method, poplar-based porous carbon materials with high specific surface area and excellent electrical properties were prepared, which solved the problems of small specific surface area and poor rate performance of existing wood-based carbon materials, and was suitable for high-efficiency charge storage applications.

CN119490186BActive Publication Date: 2025-03-28BEIHUA UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510082033.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-03-28
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The specific surface area of ​​existing wood-based carbon materials is relatively small and have poor rate performance, making it difficult to meet the needs of efficient charge storage.

Method used

Pore-filled base is stably performed by DC arc method high-temperature discharge pretreatment and salt template method, and combined with the synergistic reaction of potassium oxalate and calcium carbonate, a poplar-based porous carbon material is prepared to achieve precise regulation of the internal structure of the wood and the optimization of the pore structure.

Benefits of technology

The prepared poplar-based porous carbon material has suitable micro-mesporous ratio and good cycling stability, which improves specific surface area and electrical properties, and is suitable for electrode materials of supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490186B_ABST
    Figure CN119490186B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a poplar-based porous carbon material, comprising the following steps: (1) pretreating poplar wood chips by a direct current arc method: placing a poplar wood chip as an anode and a high-purity tungsten rod as a cathode in a direct current arc device, starting the power supply and striking the arc, and reacting to obtain arc-carbonized poplar wood chips; (2) using the arc-carbonized poplar wood chips prepared in step (1) as a raw material, and placing them in a mixed salt solution containing LiCl and ZnCl2 for immersion; then placing the mixture in a high-pressure reactor, and using a blast drying oven for hydrothermal reaction to obtain arc poplar-derived hydrothermal carbon; (3) using the arc poplar-derived hydrothermal carbon prepared in step (2) as a raw material, and placing them in a mixed solution containing potassium oxalate and calcium carbonate for immersion; then placing them in a tubular furnace for calcination to obtain a poplar-based porous carbon material. The poplar-based porous carbon material prepared by the present invention has a hierarchical network pore structure, excellent thermal stability, and exhibits excellent electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparing carbon nanomaterials by a direct current arc method, and specifically relates to a method for preparing a poplar-based porous carbon material. Background Art

[0002] In the DC arc method, the cathode usually uses a tungsten rod or a graphite rod, and the anode is composed of raw materials. The reaction mechanism is that under a certain inert atmosphere and pressure, the cathode and anode continuously discharge arcs to generate ultra-high temperatures, causing the anode raw materials to evaporate, decompose, gasify, and consume, and then through a series of physical and chemical reaction processes, the corresponding products are generated in the cathode part and inside the discharge chamber. In short, it is the process of ultra-fine particleization of materials at ultra-high temperatures (the medium is hydrogen and nitrogen high-temperature plasma). The gas atmosphere for preparing materials by DC arc discharge is generally an inert gas, such as He, Ar, N2, H2 / He, H2 / Ar, H2 / Ne, etc.; the reaction parameters generally include arc voltage, current, gas type, gas pressure, etc. Researchers have achieved high-purity and high-yield preparation of new carbon materials by changing raw materials, reaction environment, anode material, adjusting the gas intake method, etc.

[0003] As an efficient physical vapor evaporation technology, DC discharge is not only used to develop new carbon nanomaterials, but also a widely used method in the preparation of various carbon nanocomposites. Compared with the traditional synthesis methods of carbon nanomaterials, DC arc has outstanding advantages, such as: (1) the ultra-high reaction temperature of the discharge process helps to improve the graphitization degree of the material and prepare carbon nanomaterials with low structural defects; (2) the preparation parameters such as reaction raw materials and gas atmosphere can be adjusted according to the preparation needs, and the reaction time is extremely short, which is convenient for experimental personnel to operate while achieving the effect of time-saving and efficient preparation. It is a kind of environmentally friendly synthesis technology that can be scaled and industrialized; (3) the preparation cost is low, resource-saving and environmentally friendly. But relatively speaking, its disadvantages are also obvious, mainly: (1) droplets splash out from the molten pool during the discharge process, resulting in large particles in the material, affecting the product quality; (2) the product has many impurities and limited purity.

[0004] At present, DC arc is a unique technology for preparing various nanomaterials. So far, DC arc method has been used to synthesize a variety of functional nanoparticles, and has been widely used in the preparation of nanoparticles; however, it is still in the exploratory stage in the field of biomass carbon materials. Summary of the invention

[0005] In view of the problems of small specific surface area and poor rate performance of currently prepared wood-based carbon materials, the present invention relies on the natural pores of the wood itself to build an interconnected and efficient ion transmission network. Through high-temperature discharge pretreatment by direct current arc method and stabilization of the substrate by salt template method for pore filling, precise regulation of the internal structure of the wood is achieved, and starting from the pits on the longitudinally arranged pore walls of the wood, artificial customized pore making is achieved; subsequently, the further synergistic reaction of potassium oxalate activator and calcium carbonate is combined to prepare the wood-based porous carbon material with a suitable micro-mesopore ratio and good cyclic stability. The present invention broadens the scope of application of the direct current arc method and provides theoretical support for the preparation of biomass carbon materials by high-temperature thermal shock.

[0006] The present invention provides a method for preparing a poplar-based porous carbon material. The method uses a direct current arc device, uses a solid raw material poplar wood slice as an anode, and a high-purity tungsten rod as a cathode, and realizes carbonization of the anode raw material in an inert gas atmosphere under a vacuum environment to obtain a poplar-based porous carbon material.

[0007] Furthermore, the method comprises the following steps:

[0008] (1) Pretreatment of poplar wood chips by direct current arc method: Poplar wood chips are used as anodes and high-purity tungsten rods are used as cathodes in a direct current arc device. After the reaction chamber of the arc device is in a vacuum state, an inert gas is filled in as a working gas, the power supply is started and the arc is struck. During the reaction, the current and the distance between the two electrodes are regulated. After the reaction is completed, the power supply is turned off. After the temperature inside the reaction chamber is cooled to room temperature, a passivation gas is introduced for passivation treatment to obtain arc carbonized poplar wood chips;

[0009] (2) The arc carbonized poplar wood chips prepared in step (1) are used as raw materials and are immersed in a mixed salt solution containing LiCl and ZnCl2; the mixture is then placed in a high-pressure reactor and subjected to a hydrothermal reaction in a forced air drying oven to obtain arc poplar wood-derived hydrothermal carbon;

[0010] (3) The arc poplar-derived hydrothermal carbon prepared in step (2) is used as a raw material and is immersed in a mixed solution containing potassium oxalate and calcium carbonate; then, it is placed in a tubular furnace for calcination to obtain a poplar-based porous carbon material.

[0011] Preferably, in step (1), the raw material poplar wood chips are first immersed in water for 1 to 24 hours to ensure that the water fills the interior of the wood chips and improves their conductivity, and then they are placed in a DC arc device as an anode.

[0012] Preferably, in step (1), the arc reaction conditions are: the poplar wood chips are prepared into a block of 2×2×0.2 cm, the inter-electrode distance is 1-10 mm, the discharge current is 10-60 A, the arc discharge time is 5-30 s, the inert gas is high-purity argon, and the filling pressure is 40-80 KPa. Among them, the appropriate inter-electrode distance facilitates the arc stabilization after the positive and negative electrodes contact and start the arc. Adjusting the discharge current and discharge time can avoid the anode material from being eroded and pierced under high current, and can maintain the integrity of the material morphology. And the appropriate inert gas pressure is conducive to the inert gas always filling the DC arc reaction chamber to ensure the normal arc reaction process.

[0013] Preferably, in step (1), the passivation gas is a single high-purity argon gas, and the passivation time is 5 to 7 hours.

[0014] Preferably, in step (2), the conditions for preparing arc poplar wood derived hydrothermal carbon are as follows: the mixed salt solution is uniformly stirred for 30 min, the mass of the mixed salt is 6.0 g, the mass ratio of LiCl and ZnCl2 is 1:1 (i.e., 3.0 g of LiCl and 3.0 g of ZnCl2 respectively), the arc carbonized poplar wood chips are mixed and impregnated with the salt solution for 4 h, the hydrothermal reaction temperature is 200 °C, and the hydrothermal reaction time is 10 h. LiCl and ZnCl2 act as salt templates to stabilize the material base and achieve the regulation of the material morphology and pore structure. The material skeleton support provided during high-temperature pyrolysis ensures that the carbon material does not collapse and block the pores. In addition to the supporting functions of filling the material pores and stabilizing the base, the salt template also preliminarily develops the material pore size to a certain extent, promoting the generation of abundant micropores and a small amount of mesopores inside the material.

[0015] Preferably, in step (3), the mass ratio of the arc poplar wood derived hydrothermal carbon, potassium oxalate and calcium carbonate is 1:3.5:1, and the impregnation time is 4 hours. The activating agent potassium oxalate and calcium carbonate further react and decompose under high temperature pyrolysis, and the generated intermediate products (such as K2Ca(CO3)2, K2Ca2(CO3)3 and CaO) change the original size and morphology of the template particles, prompting the material to further form a hierarchical porous structure with interconnected mesopores and macropores.

[0016] It should be noted that in the experimental stage, different ratios such as 1:1.5:1, 1:2.5:1, and 1:3.5:1 were used to prepare poplar-based porous carbon materials. The experimental results show that if the amount of activator is too small, it is difficult to play a beneficial role in regulating the pore structure of the material, that is, to promote the expansion of the micropores to further generate mesopores; if the amount of activator is too much, it will lead to a strong activation etching effect that erodes the internal pores of the material, causing the original interconnected pore structure to disintegrate and collapse. The poplar-based carbon material prepared at a ratio of 1:3.5:1 has a reasonable mesopore ratio and a high specific surface area, so this ratio is used.

[0017] Preferably, in step (3), the calcination temperature is 800°C and the calcination time is 100-150 min.

[0018] The present invention also provides a poplar-based porous carbon material prepared by the method, the specific surface area of ​​which is up to 575 m 2 g -1 The mesopore volume accounts for 54.27% and the micropore volume accounts for 45.72%.

[0019] The present invention also provides application of the poplar-based porous carbon material as a capacitor electrode material.

[0020] The present invention has the following beneficial effects:

[0021] (1) The present invention first performs arc discharge pretreatment on the poplar wood chips, which has a high reaction rate, and the material morphology can be controlled, which has a certain activation and expansion effect on the pore structure of the material. Then, the salt template method is used to achieve material morphology control and stabilization of the pore structure. Then, high-temperature pyrolysis carbonization is performed, that is, micropores are retained on the basis of arc treatment, and the transformation of some micropores to mesopores is achieved, and an ideal pore structure of coexistence of mesopores and micropores is obtained.

[0022] (2) The role of salt template treatment in improving material performance is as follows: 1. As a hard template, it plays the role of filling the material pores, stabilizing the base, and supporting the skeleton, so that the obtained poplar-based layered porous carbon exhibits a hierarchical pore structure. 2. As a pore-increasing agent, it initially develops the material pore size and promotes the generation of abundant micropores and a small amount of mesopores inside the material. The high micropore porosity can provide sufficient space for charge storage, produce a higher capacitance value, and improve the electrical performance of the material.

[0023] (3) The poplar-based porous carbon material prepared by the present invention has a layered network pore structure, excellent thermal stability, and exhibits excellent electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a cross-section SEM image of the poplar-based porous carbon material YD-C synthesized in Example 1.

[0025] Figure 2 This is a SEM image of the longitudinal section of the poplar-based porous carbon material YD-C synthesized in Example 1.

[0026] Figure 3 This is the Raman spectrum of the poplar-based porous carbon material YD-C synthesized in Example 1.

[0027] Figure 4 This is the cycle performance diagram of the poplar-based porous carbon material YD-C synthesized in Example 1.

[0028] Figure 5 This is a cross-section SEM image of the poplar-based porous carbon material YD-SC synthesized in Example 3.

[0029] Figure 6 This is a SEM image of the longitudinal section of the poplar-based porous carbon material YD-SC synthesized in Example 3.

[0030] Figure 7 This is the cycle performance diagram of the poplar-based porous carbon material YD-SC synthesized in Example 3. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the contents described above.

[0032] Example 1

[0033] A method for preparing a poplar-based porous carbon material comprises the following steps:

[0034] (1) The cathode and cathode electrodes are placed inside the reaction chamber of the DC arc device. A fully soaked poplar wood chip with a size of 2 × 2 × 0.2 cm is used as the anode material and placed in a copper pot. A high-purity tungsten rod is used as the cathode.

[0035] (2) Before the experiment begins, evacuate and repeatedly purge the air in the reaction chamber. After the purge is completed, stop evacuating and introduce working gas (argon) with the gas pressure set to 80 KPa.

[0036] (3) Start the circulating cooling water system, connect the power supply and start the arc, adjust the initial current to 60 A, the working voltage to 30 V, the inter-electrode distance to 1 mm, the discharge current to 60 A and stabilize the arc to achieve arc carbonization of the poplar wood chips.

[0037] (4) After the reaction was completed, the arc carbonized poplar wood chips were collected after passivation treatment in a single argon atmosphere for 6 h.

[0038] (5) The arc carbonized poplar wood chips prepared in step (4) were used as raw materials and carbonized at 800 °C for 120 min in a tubular furnace under a nitrogen atmosphere. The collected product was a poplar-based porous carbon material (named YD-C).

[0039] Figure 1 This is a cross-section SEM image of the poplar-based porous carbon material YD-C synthesized in Example 1. Figure 2 This is a SEM image of the vertical section of the poplar-based porous carbon material YD-C synthesized in Example 1. Figure 1 and Figure 2It can be seen that the internal structure of the prepared poplar-based porous carbon material is loose and porous, the pores are evenly distributed, and the pore size difference is not large. This confirms that the effect of "secondary pore creation" can be effectively improved by arc discharge pretreatment of poplar wood followed by high-temperature pyrolysis and carbonization.

[0040] The Raman spectrum of YD-C is shown in Figure 3 As shown in the figure, it can be seen that after arc treatment, the defect level is high, the material structure tends to be disordered, and the degree of graphitization is low. The specific surface area of ​​the poplar-based porous carbon material YD-C is 708 m 2 g -1 Its pore structure is mainly mesopores, and the mesopore volume accounts for 57.07%. The detailed data are shown in Table 1.

[0041] When it is used as an electrode material for supercapacitors, the mass specific capacitance is 82550.06 mF g -1 (i.e. 82.55 Fg -1 ), the area specific capacitance is 6389.38 mF cm -2 , see Table 2 for details. Its overall specific capacitance is low, which is related to its mesoporous pore structure and low degree of graphitization. Figure 4 As shown in the figure, after 2000 long cycles, its capacitance retention rate decayed to 95.76%.

[0042] Table 1 Pore structure characteristics of poplar-based porous carbon-carbon material YD-C

[0043]

[0044] Table 2 Mass specific capacitance and area specific capacitance of poplar-based porous carbon material YD-C

[0045]

[0046] Example 2

[0047] A method for preparing a poplar-based porous carbon material comprises the following steps:

[0048] (1) Dry poplar wood chips with a size of 2 × 2 × 0.2 cm were used as raw materials. The mass ratio of raw materials to salt template (LiCl / ZnCl2 was 1:1, i.e., 3.0 g of LiCl and 3.0 g of ZnCl2) was 1:2. The raw materials were immersed in the salt template mixed solution for 30 min.

[0049] (2) The mixture of the two was placed in a high-pressure reactor and subjected to a hydrothermal reaction in a forced air drying oven at 200 °C for 10 h. After the reaction was completed, the poplar-derived hydrothermal carbon (named CW-Y2) was collected.

[0050] (3) The poplar-derived hydrothermal carbon prepared in step (2) was used as a raw material, and the mass ratios of the raw material, potassium oxalate, and calcium carbonate were 1:1.5:1, 1:2.5:1, and 1:3.5:1, respectively; the raw material was then immersed in a mixed solution of potassium oxalate and calcium carbonate for 4 h; and then carbonized at 800 °C in a tubular furnace under a nitrogen atmosphere for 2 h to obtain a poplar-based porous carbon material (named CW-1.5Y2, CW-2.5Y2, and CW-3.5Y2, respectively, according to the different ratios of the raw material to the activator).

[0051] As shown in Table 3, among the three different ratios of the poplar-based porous carbon materials, CW-3.5Y2 has the highest specific surface area of ​​296 m 2 g -1 , the pore structure is mainly mesopores and supplemented by micropores (micropore volume accounts for 37.08%, and mesopore volume accounts for 62.92%). As the dosage of potassium oxalate increases from 1:1.5:1, 1:2.5:1 to 1:3.5:1, the micropore volume of carbon materials first increases and then decreases, from 54.84% of CW-1.5Y2 to 37.08% of CW-3.5Y2; while the mesopore volume first decreases and then gradually increases, from 45.16% of CW-1.5Y2 to 33.13% of CW-2.5Y2, and then rises to 62.92% of CW-3.5Y2. This result shows that the increase of activator is conducive to the expansion of micropore diameter, prompting the poplar-based carbon material to generate abundant mesopores; on the other hand, it also shows that the strong etching effect between excessive activator and carbon wall often leads to the collapse of pore structure. The above results indicate that the dosage of activator is the key to regulating the pore structure, and poplar-based carbon materials with high specific surface area can be prepared by salt template-assisted activator activation.

[0052] When the prepared poplar-based porous carbon materials with different ratios were used as electrode materials for supercapacitors, CW-3.5Y2 had the highest specific capacitance, with a mass specific capacitance of up to 101406.25 mF g -1 (i.e. 101.40 F g -1 ), the area specific capacitance reaches 5070.31 mF cm -2 , see Table 4 for details. This is related to its high specific surface area and hierarchical pore structure with coexistence of meso-micropores.

[0053] In view of the above experimental results, the poplar-based carbon material obtained at a ratio of 1:3.5:1 has a reasonable meso / micropore ratio and a high specific surface area. Therefore, in Example 3, this ratio is used in combination with a DC arc method to prepare a poplar-based porous carbon material having high specific capacitance, large specific surface area and excellent electrode performance.

[0054] Table 3 Pore structure characteristics of poplar-based porous carbon-carbon materials

[0055]

[0056] Table 4 Mass specific capacitance and area specific capacitance of poplar-based porous carbon materials

[0057]

[0058] Example 3

[0059] A method for preparing a poplar-based porous carbon material comprises the following steps:

[0060] (1) Place the positive and negative electrodes inside the reaction chamber of the DC arc equipment, use a completely soaked poplar wood chip as the anode material and place it in a copper pot, and use a high-purity tungsten rod as the cathode.

[0061] (2) Before the experiment begins, evacuate and repeatedly purge the air in the reaction chamber. After the purge is completed, stop evacuating and introduce working gas (argon) with the gas pressure set to 80 KPa.

[0062] (3) Start the circulating cooling water system, connect the power supply and start the arc, adjust the initial current to 60 A, the working voltage to 30 V, the inter-electrode distance to 1 mm, the discharge current to 60 A and stabilize the arc to achieve arc carbonization of the poplar wood chips.

[0063] (4) After the reaction was completed, the arc carbonized poplar wood chips were collected after passivation treatment in a single argon atmosphere for 6 h.

[0064] (5) The arc carbonized poplar wood chips prepared in step (4) are used as raw materials, and the mass ratio of the raw materials to the salt template (the mass ratio of LiCl / ZnCl2 is 1:1, that is, 3.0 g of LiCl and 3.0 g of ZnCl2) is 1:2. The raw materials are placed in the salt template mixed solution and soaked for 30 min; then the mixture of the two is placed in a high-pressure reactor and subjected to a hydrothermal reaction in a forced air drying oven at 200 °C for 10 h; after the reaction is completed, the arc poplar wood-derived hydrothermal carbon is collected.

[0065] (6) The arc poplar-derived hydrothermal carbon prepared in step (5) was used as a raw material, and the mass ratio of the raw material, potassium oxalate, and calcium carbonate was 1:3.5:1; the raw material was placed in a mixed solution of potassium oxalate and calcium carbonate and impregnated for 4 h; then, the raw material was carbonized at 800 °C in a tubular furnace under a nitrogen atmosphere for 2 h, and a poplar-based porous carbon material (named YD-SC) was collected.

[0066] Figure 5 This is a cross-section SEM image of the poplar-based porous carbon material YD-SC synthesized in Example 3. Figure 6This is a SEM image of the poplar-based porous carbon material YD-SC after longitudinal section synthesized in Example 3. It can be seen from the figure that the cross section of the poplar-based porous carbon material presents a loose and porous mesh-like cross-linked interconnected structure, and the original morphology of the wood is well preserved. The DC arc high-temperature discharge pretreatment method is used to activate the internal moisture and related components of the wood, and the secondary pore formation of the wood is achieved, which is specifically manifested in the fragmentation of the film on the inner wall of the pores on the longitudinal section.

[0067] As shown in Table 3, the specific surface area of ​​the poplar-based porous carbon material YD-SC is 575 m 2 g -1 The micropore ratio of the material YD-C obtained in Example 1 is significantly improved. The meso-micropore ratio is close to equilibrium, and the pore structure is in a relatively ideal state. For details, please refer to Table 5. When it is used as an electrode material for supercapacitors, the mass specific capacitance is as high as 159066.96 mFg -1 (i.e. 159.06 F g -1 ), the area specific capacitance reaches 11134.69 mF cm -2 , see Table 6 for details. Its specific capacitance is much higher than that of YD-C, which is related to its ideal pore structure with coexistence of meso-micropores. The cycle performance diagram of YD-SC is shown in Figure 7 As shown in the figure, after 2000 long cycles, the capacitance retention rate is as high as 98.36%, indicating its excellent long cycle stability.

[0068] Table 5 Pore structure characteristics of poplar-based porous carbon-carbon material YD-SC

[0069]

[0070] Table 6 Mass specific capacitance and area specific capacitance of poplar-based porous carbon material YD-SC

[0071]

[0072] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a poplar-based porous carbon material, characterized in that: The method comprises the following steps: (1) Pretreatment of poplar wood chips by direct current arc method: Poplar wood chips are used as anodes and high-purity tungsten rods are used as cathodes in a direct current arc device. After the reaction chamber of the arc device is in a vacuum state, an inert gas is filled in as a working gas, the power supply is started and the arc is struck. During the reaction, the current and the distance between the two electrodes are regulated. After the reaction is completed, the power supply is turned off. After the temperature inside the reaction chamber is cooled to room temperature, a passivation gas is introduced for passivation treatment to obtain arc carbonized poplar wood chips; (2) The arc carbonized poplar wood chips prepared in step (1) are used as raw materials and are immersed in a mixed salt solution containing LiCl and ZnCl2; the mixture is then placed in a high-pressure reactor and subjected to a hydrothermal reaction in a forced air drying oven to obtain arc poplar wood-derived hydrothermal carbon; (3) The arc poplar-derived hydrothermal carbon prepared in step (2) is used as a raw material and is immersed in a mixed solution containing potassium oxalate and calcium carbonate; then, it is placed in a tubular furnace for calcination to obtain a poplar-based porous carbon material.

2. The method for preparing a poplar-based porous carbon material according to claim 1, characterized in that: In step (1), the raw material poplar wood chips are first immersed in water for 1 to 24 hours, and then placed in a DC arc device as an anode.

3. The method for preparing a poplar-based porous carbon material according to claim 1, characterized in that: In step (1), the arc reaction conditions are: the distance between the two electrodes is 1-10 mm, the discharge current is 10-60 A, the arc discharge time is 5-30 s, the inert gas is high-purity argon, and the filling pressure is 40-80 KPa.

4. The method for preparing a poplar-based porous carbon material according to claim 1, characterized in that: In step (1), the passivation gas is a single high-purity argon gas, and the passivation time is 5 to 7 hours.

5. The method for preparing a poplar-based porous carbon material according to claim 1, characterized in that: In step (2), the conditions for preparing arc poplar wood derived hydrothermal carbon are as follows: the mixed salt solution is uniformly stirred for 30 min, the mass ratio of LiCl and ZnCl2 in the mixed salt is 1:1, the arc carbonized poplar wood chips are mixed and immersed in the salt solution for 4 h, the hydrothermal reaction temperature is 200 ° C, and the hydrothermal reaction time is 10 h.

6. The method for preparing a poplar-based porous carbon material according to claim 1, characterized in that: In step (3), the mass ratio of the arc poplar wood derived hydrothermal carbon, potassium oxalate and calcium carbonate is 1:3.5:1, and the impregnation time is 4 hours.

7. The method for preparing a poplar-based porous carbon material according to claim 1, characterized in that: In step (3), the calcination temperature is 800°C and the calcination time is 100-150 min.

Citation Information

Patent Citations

  • Preparation method of poplar-based porous carbon material and product of poplar-based porous carbon material

    CN109319783A